Self-Administered Tinnitus Pitch Matching versus a Conventional Audiometric Procedure. - Kim, Tae Su; Yakunina, Natalia; Ryu, Yoon-Jong; Chung, Ik Joo; Nam, Eui-Cheol (Audiology & Neurotology, 2017)
Objective: Obtaining an accurate tinnitus pitch match is an initial and critical requirement for tinnitus evaluation and treatment, particularly for applying tailor-made notched music training. We investigated whether computer-based self-administered tinnitus pitch matching (CSTPM) is comparable with a conventional audiometric procedure (CAP).Methods: In total, 82 patients (mean age 45.52 years; 42 females) with tonal tinnitus participated. The CAP was performed by the same audiologist using a 2-alternative forced choice method with a frequency range of 0.25-16 kHz. In the CSTPM, the subjects used personal computer software with a scrolling slider to select the sound closest to their tinnitus pitch. After each matching procedure, an octave challenge test was applied. A multivariate logistic regression was performed to determine factors associated with the difference between the CSTPM and CAP.Results: The subjects' mean hearing threshold was 21.25 ± 17.61 dB HL; the mean tinnitus handicap inventory score was 35.56 ± 24.09. The mean pitches measured with the CSTPM and CAP were 6.29 ± 4.30 and 6.98 ± 5.33 kHz, respectively. In total, 57 (69.5%) subjects matched their tinnitus with less than half an octave difference between the procedures. The results of the 2 methods correlated significantly with each other (Pearson r = 0.793, p < 0.001). Octave confusion was a significant factor affecting the difference between the procedures (odds ratio 8.92, p < 0.05).Conclusions: The CSTPM appears to be as accurate as the standard audiological procedure, and may be used instead of the CAP when octave confusion is minimized.